A human pseudoautosomal gene, ADP/ATP translocase, escapes X-inactivation whereas a homologue on Xq is subject to X-inactivation - Schiebel, Katrin; Weiß, Birgit; Steinbach, Doris; Rappold, Gudrun (Nature genetics, 1993)
We report the cloning of a highly conserved pseudoautosomal gene on the human sex chromosomes. A cDNA clone was selected by crosshybridization with a microdissected clone from the chromosomal subregion Xp22.3. It encodes a previously characterized member of the ADP/ATP translocase family and plays a fundamental role in cellular energy metabolism. This gene, ANT3, is located approximately 1,300 kilobases from the telomere, proximal to the pseudoautosomal gene CSF2RA, and escapes X-inactivation. Interestingly, a homologue of ANT3, ANT2, maps to Xq and is subject to X-inactivation. These genes provide the first evidence of two closely related X-chromosomal genes, which show striking differences in their X-inactivation behaviour.
Gesehen am 30.03.2021